Evolution of Mind, Brain, and Culture - Pittman, Holly; Hatfield, Gary C. (Gary Carl) (Book collections on Project MUSE., 2013)
Evolution of Mind, Brain, and Culture draws together studies in archaeology, anthropology, psychology, philosophy, genetics, neuroscience, and environmental science to investigate the evolution of the human mind, the brain, and the human capacity for culture.